SOCIAL PSYCHOLOGICAL MECHANISMS OF DEVELOPMENT OF LOGICAL THINKING IN PRESCHOOL CHILDREN - Askarov Anvarjon Rahimjon ogli (Galaxy International Interdisciplinary Research Journal, 2022)
Often mental training means a child’s worldview, knowledge of living nature, people and their work. This knowledge can be the basis of school education, but vocabulary and ability to perform certain actions are not the main indicators of a child’s mental readiness for school. The school curriculum requires children to be able to compare, analyze, generalize, draw certain conclusions, as well as sufficiently developed cognitive processes.